Efficacy of psychosocial interventions for psychological and pregnancy outcomes in infertile women and men: a systematic review and meta-analysis. Issue 1 (28th January 2015) - Frederiksen, Yoon; Farver-Vestergaard, Ingeborg; Skovgård, Ninna Grønhøj; Ingerslev, Hans Jakob; Zachariae, Robert
Abstract : Objective: To evaluate the evidence on the efficacy of psychosocial interventions for improving pregnancy rates and reducing distress for couples in treatment with assisted reproductive technology (ART). Design: Systematic review and meta-analysis. Data sources: PsycINFO, PubMed, EMBASE, CINAHL, Web of Science and The Cochrane Library between 1978 and April 2014. Study selection: Studies were considered eligible if they evaluated the effect of any psychosocial intervention on clinical pregnancy and/or distress in infertile participants, used a quantitative approach and were published in English. Data extraction: Study characteristics and results were extracted and the methodological quality was assessed. Effect sizes (ES; Hedges g) were pooled using a random effects model. Heterogeneity was assessed using the Q statistic and I 2, and publication bias was evaluated using Egger's method. Possible moderators and mediators were explored with meta-analyses of variances (ANOVAs) and meta-regression. Results: We identified 39 eligible studies (total N=2746 men and women) assessing the effects of psychological treatment on pregnancy rates and/or adverse psychological outcomes, including depressive symptoms, anxiety, infertility stress and marital function. Statistically significant and robust overall effects of psychosocial intervention were found for both clinical pregnancy (risk ratio=2.01; CI 1.48 to 2.73; p<0.001) and combined psychological outcomes (Hedges g=0.59; CI 0.38 to 0.80; p=0.001). The pooled ES for psychological outcomes were generally larger for women (g: 0.51 to 0.73) than men (0.13 to 0.34), but the difference only reached statistical significance for depressive symptoms (p=0.004). Meta-regression indicated that larger reductions in anxiety were associated with greater improvement in pregnancy rates (Slope 0.19; p=0.004). No clear-cut differences were found between effects of cognitive–behavioural therapy (CBT; g=0.84), mind–body interventions (0.61) and other intervention types (0.50). Conclusions: The present meta-analysis suggests that psychosocial interventions for couples in treatment for infertility, in particular CBT, could be efficacious, both in reducing psychological distress and in improving clinical pregnancy rates.